Assessment of Pseudoscientific Beliefs Among University Students in Northeastern Mexico - José Antonio Azuela; Wendy Xiomara Chavarría-Garza; Osvaldo Aquines-Gutiérrez; Ayax Santos-Guevara; Humberto Martínez-Huerta (Education Sciences)
This study examines pseudoscientific beliefs among university students, focusing on gender and faculty differences at a private university in northeastern Mexico. Data were collected from 794 students (38% male, 62% female) across six academic disciplines using the Pseudoscience Endorsement Scale (PES). Statistical analyses included the Kruskal–Wallis test to assess group differences and the Wilcoxon rank sum test for pairwise comparisons. Results revealed significant gender differences (p < 0.001), with female students scoring higher. Scores also varied significantly across faculties (p < 0.001), with students in Business and Arts, Architecture, and Design exhibiting the highest levels of endorsement of pseudoscientific beliefs. In contrast, those in Engineering and Technology scored the lowest. These findings underscore the need for targeted educational interventions to mitigate pseudoscientific beliefs and enhance students’ understanding of STEM fields. The study aligns with the United Nations’ Sustainable Development Goal 4, which advocates for inclusive, equitable, and quality education that fosters critical thinking and lifelong learning. It emphasizes the importance of accounting for gender and academic background when addressing students’ belief systems.